Use of complementary and alternative medicine among patients with cancer in a sub-Himalayan state in India: An exploratory study - Pandey, Laxman (J Ayurveda Integr Med, 2021)
BACKGROUND: The use of complementary and alternative medicine (CAM) is widespread among cancer patients in India. OBJECTIVE: The present study elucidated usage patterns of CAM and the factors responsible for its adoption among the patients with cancer, and the therapeutic impact of CAM. MATERIALS AND METHODS: This was a questionnaire-based study, conducted among patients with cancer in a tertiary care hospital in a sub-Himalayan city. Data were analyzed using statistical methods. RESULTS: A total of 2614 patients with cancer were included. Almost half of the patients (n = 1208, 46.2%) reported to have been treated with CAM. Breast cancer (n = 274, 23.0%) was most prevalent with majority at advanced stages. Ayurveda (n = 428, 35.9%) Yoga/Naturopathy (n = 381, 32.0%) Homeopathy (n = 143, 12.0%) and Unani (n = 71, 5.9%) were used commonly. Among CAM users, 85.0% (n = 1012) of patients used CAM as the sole method of treatment, while 58.9% (n = 702) patients reported initial symptomatic benefit. CONCLUSION: Using CAM benefitted a significant number of patients with cancer. However, there is an urgent need to integrate CAM with modern system of medicine.